Civil rights literature, past & present - Varlack, Christopher Allen (Ipswich : Grey House Publishing, Inc., 2017)
American civil rights literature has largely been associated with speeches, letters, and non-fiction works produced by African-American activists of the 1950s and 60s such as Dr. Martin Luther King, Jr. and Malcolm X. This volume not only examines key works of the African-American civil rights debate past and present, it also explores issues of gender equality and sexual orientation integral to civil rights studies. This new addition to the Critical Insights series aims to critically engage with the existing plethora of canonized literature while contemporizing the conversation with topics currently affecting our nation. Edited by Christopher Allen Varlack from the University of Maryland, Baltimore County, Critical Insights' Civil Rights Literature, Past and Present begins with two introductory essays from the editor that detail the intersection of Race, Gender, and Orientation in American civil rights literature. The remainder of the text is then split up into two sections of essays: Critical contexts, which gives users a background of the material, and Critical Readings, a selection of in-depth, theoretical examinations of civil rights literature. Each essay is 2,500 to 5,000 words in length, and all essays conclude with a list of "Works Cited," along with endnotes. Finally, the volume's appendixes offer a section of useful reference resources. -- Publisher's description.
"Caught in an inescapable network of mutuality": the intersection of race, gender, and orientation in American civil rights literature / Christopher Allen Verlack -- Free speech and racial rhetoric: African-American writers on race in the United States / Kavon Franklin -- Inadequate conception of human complexity: Ellison revises Elkins / Jessie LaFrance Dunbar -- "Be loyal to yourselves": Jim Crow segregation, black cultural nationalism, and US cultural memory in Ossie Davis' Purlie Victorious / Carol Bunch Davis -- Haunting America: racial identity and otherness in civic society / Mary K. Ryan -- Unpacking notions of citizenship through James Baldwin's Another Country / Hope W. Jackson -- "On revolution and equilibrium": Barbara Deming's secular nonviolence / Sheila Murphy -- "(B)ut yesterday morning came the worst news": Margaret Walker Alexander's Prophets for a New Day / Seretha D. Williams -- The mothers' tragedy: loss of a child in the works of Gwendolyn Brooks, Dudley Randall, and Michael Harper / Eric J. Sterling -- Alice Walker and Claudia Rankine: reclaiming the ocularity of the self / Margaret Cox -- "Crooning (the) lullabies (of) ghosts": reclamation and voices of witness as sociopolitical protest in the short fiction of Alice Walker / Christopher Allen Verlack -- The city and the country: queer utopian spaces in John Rechy's City of Night and Patricia Highsmith's The Price of Salt / Derrick King -- "B(l)ack up on the shelf: the erasure of black queerness in Martin Luther King, Jr.'s Why We Can't Wait / Robert LaRue -- Writing civil rights after James Byrd, after Matthew Shepard / Tasia Milton -- "The process of becoming nobody": reflections on E. Franklin Frazier's Black Bourgeoisie: the Rise of a New Middle Class / Leonard A. Stevenson -- Toward a more inclusive America: Jesse Jackson's 1984 and 1988 Democratic National Convention addresses / Enrico Beltramini -- Agency, activism, and the black domestic worker in Kathryn Stockett's The Help and Delores Phillips' The Darkest Child / Kaila Philo -- Staging MLK in the age of colorblindness: The Good Negro and The Mountaintop / Andrew Sargent -- What happens when death becomes a poem?: Understanding the place of mourning in civil rights literature / Corrie Claiborne -- Social media meets social justice: the role of the hashtag in the contemporary conversation on race / Deborah F. Kadiri.
Includes bibliographical references (pages 347-354) and index.
Keywords: Civil rights in literature; Civil rights movements in literature; American literature -- 20th century -- History and criticism; American literature -- 21st century -- History and criticism; Civil rights movements -- United States -- History -- 20th century; Civil rights movements -- United States -- History -- 21st century; Criticism, interpretation, etc; History